Framing Pernyataan Sikap SMA Tarakanita 1 Jakarta dalam Kasus AGH - Johanes, Sutanto; Purnama, Finsensius Yuli (Expose: Jurnal Ilmu Komunikasi, 2024)
The study of framing analysis in media research has proliferated, yet its application to press releases or public relations statements remains uncommon. This research aims to analyze the framing of SMA Tarakanita 1 Jakarta's position statement regarding the AGH case, which involved legal action against Mario Dandy Satriyo (20) for the alleged persecution of David Ozora (17). Employing a qualitative descriptive approach and framing analysis method by Robert N. Entman, the study examines how SMA Tarakanita 1 Jakarta selects and emphasizes certain aspects of the crisis stemming from AGH's alleged involvement in David Ozora's persecution. In addition to analyzing the primary data—the position statement text—the researcher conducted multiple in-depth interviews with the Chairperson of the Tarakanita Crisis Center (TCC) to comprehensively explore framing and agenda setting processes. The findings reveal that SMA Tarakanita 1 Jakarta frames its position statement in the AGH case by defining the problem, making moral judgments, and recommending treatments. Interviews also unveiled Tarakanita's potential as a public relations exemplar for educational institutions in crisis management through the Tarakanita Crisis Center (TCC), aiming to safeguard the organization's reputation and image while addressing crises effectively. This underscores the importance of strategic communication and crisis response mechanisms in maintaining organizational integrity amidst challenges.